DESIGN A DEVICE FOR DETECTING PATIENT HEART RATE AND BODY TEMPERATURE BASED ON ESP-32 - Al Hakim, Daffa; Falah, Muhammad Akmal; Dzikri, Muhammad Haikal (Indonesian Journal of Electrical Engineering and Electronics, 2025)
This article discusses the development of an Internet of Things (IoT) based patient health monitoring system using ESP32 as the main microcontroller and a web server to display data in real-time. This system is equipped with a MAX 30102 sensor, DS18b20 Sensor and DHT11 Sensor, designed to measure and monitor various patient health parameters, such as body temperature, heart rate, blood pressure, and blood oxygen levels (SpO2) through sensors connected to the ESP32. Data obtained from these sensors will be sent to the web to be processed and displayed in an easy-to-understand form. With this system, it is expected to facilitate monitoring of patient health conditions remotely, and increase the efficiency of medical monitoring.